DISTRIBUTION SYSTEM HIERARCHY: SUPPLYING HEAT RELIABLY - Stanislav Chicherin; Dzhamal Abdulaev (Вестник Северо-Кавказского федерального университета, 2022)
In Russia, consumer substations are becoming more and more common in apartment buildings and other large buildings. For this reason, the literature survey was conducted on the alternative, i. e. group substations. This type is described in detail. The main reasons for the group substations are consumption measurements and renovation of domestic hot water systems. Thanks to these substations, a 2-stage network fulfilling requirements of security and hydraulic limitations is made available for the practical operation. In other words, an efficient way to decrease energy consumption is to keep distribution systems aware of the transmission ones. Low return temperature in the distribution networks are also important operational factors for obtaining an efficient district heating system.